Let x=the first number
Then x+7=second number
And 4(x+7)+2=third number (2 more than 4 times the second)
Now we are told that:
x+(x+7)+(4(x+7)+2)=85 get rid of parentheses
x+x+7+4x+28+2=85 simplify
6x+37=85 subtract 37 from each side
6x+37-37=85-37
6x=48
x=8---first number
x+7=8+7=15 second number
4(x+7)+2=4*15+2=62 third number
CK
8+15+62=85
85=85
Answer:
you ended up having = 1/n^3[1^2+2^2+3^2...(n-1)^2]
hope this helps :')
Answer:
I think A
Step-by-step explanation:
Answer:
15% per year
7.5% half year
5000 * 7.5% = $375 every 6 months.
Step-by-step explanation:
Y=1/9(-1)+4
Explanation:
X=-1 and y=8